2022
DOI: 10.22146/ipas.69078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of relay intercropping model and application of biological agents on the growth and yield of hot pepper

Abstract: Tiyung cultivar, the consumer preferences of hot pepper in Magelang Regency, is still low in productivity (7 ton.ha-1). This research aimed to determine the growth and yield of hot pepper planted in relay intercropping as affected by biological agent application as a technology to increase productivity. This research was arranged in a Factorial Randomized Complete Block Design with an intercropping pattern of hot pepper (two and three rows model). The second factor was the application of biological agents, con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…The primary crop in an intercropping system acts as a shade, affecting intermediate plants' growth and increasing stem segment length, plant height, and specific leaf area (Liu et al 2017;Sevirasari et al 2022). In addition, the influence of low light intensity can decrease photosynthesis, reducing plant growth, such as the number of leaves and branching (Fiorucci and Fankhauser 2017;Ulinnuha and Syarifah 2022).…”
Section: Morphology Trait Of Chili Peppermentioning
confidence: 99%
“…The primary crop in an intercropping system acts as a shade, affecting intermediate plants' growth and increasing stem segment length, plant height, and specific leaf area (Liu et al 2017;Sevirasari et al 2022). In addition, the influence of low light intensity can decrease photosynthesis, reducing plant growth, such as the number of leaves and branching (Fiorucci and Fankhauser 2017;Ulinnuha and Syarifah 2022).…”
Section: Morphology Trait Of Chili Peppermentioning
confidence: 99%
“…Bacillus velezensis is a Plant Growth Promoting Rhizobacteria (PGPR) that produces secondary metabolites with antibiotic properties, which can increase plant resistance and suppress growth and development of pathogens, thereby also having an impact on plant health (Wisanggeni et al, 2023). B. velezensis can also induce plant growth by increasing plants nutrient absorption by, increasing ni-trogen fixation and assisting phosphate dissolution, as well as producing the hormone Indole Acetic Acid (IAA), which can increase plant resistance induction (Sevirasari et al, 2022;Zaid et al, 2022). The use of B. velezensis by soaking and spraying application by Rahma et al (2020), reported that B. velezensis was able to suppress twisted disease and purple spots development on shallot plants by 67% and increase plant growth and protect shallot bulbs postharvest.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, land degradation also contributes to this loss. The application of an innovative strategy such as intercropping soybean with other major commodities to minimize land usage competition is therefore important to achieve sustainable land use (Srihartanto and Indradewa 2019;Astiko et al 2022) and food security (Sevirasari et al 2022).…”
Section: Introductionmentioning
confidence: 99%